Pernikahan Dini: Respons Terhadap Masalah Dilematik Antara Fikih Otoriter atau Fikih Otoritatif - Nur Kholis; Suharto, Mukhamad (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to unravel religious biases in the practice of early marriage in Indonesia and to strengthen Islamic Family Law literacy among the public. Despite the revision of the Marriage Law through Law No. 16/2019, early marriage remains widespread in Indonesia. One of the contributing factors is the community's religious understanding, rooted in authoritarian fiqh. Originally, fiqh represented a dynamic human interpretation of human problems, but it has transformed into an authoritarian understanding. This study employs a library research method, adopting a descriptive-analytic approach with a hermeneutic-negotiative framework, or progressive fiqh, as introduced by Khaled Abou El Fadl. The findings of this research reveal two key points: First, Islamic legal discourse should produce inclusive, progressive, and tolerant fiqh. Fiqh should be understood through diverse perspectives, refreshed hypotheses, and progressive legal reasoning. In contrast, authoritarianism in interpreting fiqh can stifle creativity and limit human engagement with Islamic law. Second, the government's program on Marriage Age Maturity can serve as a manifestation of the concept of